2014
DOI: 10.4103/1008-682x.122350
|View full text |Cite
|
Sign up to set email alerts
|

Help-seeking behavior for erectile dysfunction: a clinic-based survey in China

Abstract: The behavior of Chinese patients seeking help for erectile dysfunction (ED) has not been described in detail. This was an observational study conducted using an outpatient clinic-based questionnaire survey of ED patients. From 2008 to 2009, physicians in 10 medical centers in China enrolled 2693 men (aged 25–70 years) diagnosed with ED. The diagnosis was based on the International Index of Erectile Function 5 (IIEF-5) Questionnaire. The men completed a survey that asked questions about demographics, marital st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 13 publications
0
7
2
Order By: Relevance
“…Most of the patients (48%) did not refer to any source for ED information. This result differs from that of Zhang et al [25]. Zhang, Yu, He and Jin [25] showed that, among primary health care patients with ED in China, physicians (54%) were the most frequently consulted source, followed by the internet (52%) and friends (34%).…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…Most of the patients (48%) did not refer to any source for ED information. This result differs from that of Zhang et al [25]. Zhang, Yu, He and Jin [25] showed that, among primary health care patients with ED in China, physicians (54%) were the most frequently consulted source, followed by the internet (52%) and friends (34%).…”
Section: Discussioncontrasting
confidence: 58%
“…This result differs from that of Zhang et al [25]. Zhang, Yu, He and Jin [25] showed that, among primary health care patients with ED in China, physicians (54%) were the most frequently consulted source, followed by the internet (52%) and friends (34%). Only 6% of ED patients did not refer to any source [25].…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…In general population, most studies have reported more common sexual dysfunction in females than in males [35, 36]. About 20–30% of men and 40–45% of women reported at least one item of sexual dysfunction [3739]. In a previous study in India, 70% of female patients with schizophrenia reported having sexual dysfunction [40].…”
Section: Discussionmentioning
confidence: 99%
“…Existing literature supports, particularly in East Asian countries, men feeling ashamed about seeking treatment for sexual dysfunction treatment and it poses a considerable barrier for men seeking treatment. 16 17 19 20 Western studies have found feeling ashamed to be a much less frequent reason than East Asian countries. 14 15 East Asian societal perceptions that sexual activities are not important for older people may reinforce feeling ashamed and reluctance to seek treatment.…”
Section: Discussionmentioning
confidence: 99%